Principles of progenitor temporal patterning in the developing invertebrate and vertebrate nervous system. - Oberst, P.; Agirman, G.; Jabaudon, D. (Current Opinion in Neurobiology, 2019)
During the development of the central nervous system, progenitors successively generate distinct types of neurons which assemble into the circuits that underlie our ability to interact with the environment. Spatial and temporal patterning mechanisms are partially evolutionarily conserved processes that allow generation of neuronal diversity from a limited set of progenitors. Here, we review examples of temporal patterning in neuronal progenitors in the Drosophila ventral nerve cord and in the mammalian cerebral cortex. We discuss cell-autonomous mechanisms and environmental influences on the temporal transitions of neuronal progenitors. Identifying the principles controlling the temporal specification of progenitors across species, as highlighted here, may help understand the evolutionary constraints over brain circuit design and function.